2022
DOI: 10.3389/fenvs.2022.958203
|View full text |Cite
|
Sign up to set email alerts
|

Is green and sustainable technological innovation a potential driver of environmental performance? an empirical investigation across the ASEAN region

Abstract: Environmental degradation is a significant concern that jeopardizes global sustainable production and consumption. In this instance, ASEAN (Association of South-East Asian Nations) has contributed to a considerable amount of carbon dioxide (CO2) emissions throughout the modernization phase. However, there is a paucity of information within this region on the non-linear impact of transitions in green and sustainable technological innovation on CO2 emissions. In response, the present work endeavors to bridge the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Therefore, the individual uses of gardens in the original plans were separated from the rest of the city plans. In the 21st century, there is a renewed emphasis on mixed functions Rehman and Holy, 2022).…”
Section: Historical Development Of Public and Green Spacementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the individual uses of gardens in the original plans were separated from the rest of the city plans. In the 21st century, there is a renewed emphasis on mixed functions Rehman and Holy, 2022).…”
Section: Historical Development Of Public and Green Spacementioning
confidence: 99%
“…The tendency towards private living measures, jobs in isolated offices and the increasing fame of coaches as the main means of conveyance contribute to this segregation. Phenomena such as high traffic load, noise, deprived air quality, the temperature rises, and violence are more public in cities than in rural areas (Jennings et al, 2012;Kallio et al, 2016;Besir and Cuce, 2018;Antón et al, 2022;Rehman and Holy, 2022). On the other hand, cities deal with many buildings that brand life easier than life in the countryside-the reason of cities expansion.…”
Section: Introductionmentioning
confidence: 99%
“…This topic arouses great interest among the Arabian population. The forest's healing effect is described in many research articles, which simultaneously found the healing bond between man and nature, with much focus on nature ( 6 , 7 ). Interest in the health effects of the forest is present in Arabian society.…”
Section: Introductionmentioning
confidence: 99%
“…A thorough discussion about the impact of smart cities and the environment is discussed by Yamagata and Seya (2013) and Shamsuzzoha et al (2021), who highlight the merits and demerits of cities. Chen et al (2020), Rehman and Holy (2022), Farkas et al (2023), Grigoletto et al (2023), and Honey-Rosés and Zapata (2023) have suggested many corrective measures that should be taken to reduce air pollution and develop smart cities.…”
Section: Introductionmentioning
confidence: 99%